How is Augmented Reality Developed in Physics Education? A Review with NVivo from 2019-2024 - Aminudin, Adam Hadiana; Syamsiah, Endah Nur; Nabilah, Fatih Najah; Samsudin, Achmad (Jurnal Pendidikan MIPA, 2024)
This review aims to identify developments in Augmented Reality (AR) in physics education from 2019-2024 through NVivo analysis. A total of 19 articles from the Scopus database (SJR 2023: 2 (Q1), 6 (Q2), 4 (Q3), and 7 (Not Applicable)) were used in this review and filtered through the prism guide. The focus of this review includes: 1) The Aim; 2) Methods; 3) Participants; 4) Instruments; 5) Analysis; 6) Concept, and; 7) Software or Device. The results of this review explain that: 1) Based on the objective, the application used is AR (89%); 2) The method used is the development method (47%); 3) Most participants are high school students (42%); 4) The instruments used were questionnaires (37%); 5) N-gain analysis is the most widely used analysis (11%); 6) The physics concept used is electricity (16%), and; 7) The software or device used is 3D Blender (16%) and Unity (16%). Thus, we concluded that the development of AR for physics concepts has become interesting research over the last 5 years (2019-2024). The recommendation from this review is that when developing AR in physics learning, especially abstract ones, you can conduct research using development methods and 3D Blender and Unity software.         Keywords: augmented reality, physics education, NVivo analisis.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp582-600